Biological variation: Understanding why it is so important? - Badrick, Tony (Practical laboratory medicine, 2021)
This Review will describe the increasing importance of the concepts of biological variation to clinical chemists. The idea of comparison to ‘reference’ is fundamental in measurement. For the biological measurands, that reference is the relevant patient population, a clinical decision point based on a trial or an individual patient’s previous results. The idea of using biological variation to set quality goals was then realised for setting Quality Control (QC) and External Quality Assurance (EQA) limits. The current phase of BV integration into practice is using Patient-Based Real-Time Quality Control (PBRTQC) and Patient Based Quality Assurance (PBQA) to detect a change in assay performance. The challenge of personalised medicine is to determine an individual reference interval. The Athletes Biological Passport may provide the solution.